Anticipating serve direction: implicit sequence learning in tennis - Jackson, R. C.; Gudgeon, M. (Journal of Sports Sciences, 2006)
One of the skills that separates experts from their less skilled counterparts is the ability to anticipate key events. Research has established that experts display greater sensitivity to advance postural cues, and also make greater use of situational probabilities and contextual game-related information than novices (Williams & Grant, 1999, International Journal of Sport Psychology, 30, 194-220). Currently, there is a debate over how such skills are learned and hence how they should be coached. Specifically, it has been suggested that anticipation may largely be learned implicitly, that is, experts may become sensitive to subtle postural cues or situational probabilities without necessarily intending to do so and in such a way that the resulting knowledge is difficult to express (Berry & Dienes, Implicit learning : Theoretical and empirical issues, 1993, Hove : Lawrence Erlbaum Associates). Thus far, there is no clear evidence of implicit learning in the anticipation literature, therefore, the aim of the present study was to examine whether implicit learning of a serve location sequence would occur in tennis players.